Mycobacterium tuberculosis strains disrupted in mce3 and mce4 operons are attenuated in mice - Ryan H. Senaratne; Ben S. Sidders; Patrícia Carvalho de Sequeira; G. F. T. Saunders; Kathleen Y. Dunphy; Olivera Marjanovic; J. Rachel Reader; Patricia Lima; Stephen Chan; Sharon L. Kendall; Johnjoe McFadden; Lee W. Riley (2008)
The Mycobacterium tuberculosis genome contains four copies of an operon called mce (mce1-4). Previously we reported that M. tuberculosis disrupted in the mce1 operon is more virulent than wild-type M. tuberculosis in mice. We generated single deletion mutants in mce3 (Deltamce3) and mce4 (Deltamce4) operons and a double deletion mutant (Deltamce3/4). Similar doubling times and growth characteristics were observed for all mutants and the wild-type (parent) M. tuberculosis H37Rv strain in culture and in macrophages. In addition, similar bacterial burdens were detected in organs from mice infected with Deltamce3 and the parent strain. However, the bacterial burdens of mice infected with Deltamce4 and Deltamce 3/4 were less than those of mice infected with the parent strain. The median survival times of mice infected with wild-type M. tuberculosis, Deltamce3, Deltamce4 and Deltamce3/4 were 40.5, 46, 58 and 62 weeks, respectively. Histopathological examination of lungs at 15 weeks post-infection showed that the extent of the lung lesions was less prominent in mice infected with Deltamce4 and Deltamce 3/4 mutants than in mice infected with the other two strains. These observations suggest that the mce3 and mce4 operons have a role distinct from that of mce1 for in vivo survival of M. tuberculosis.